2021
DOI: 10.1002/cam4.4169
|View full text |Cite
|
Sign up to set email alerts
|

The antitumor mechanisms of aerobic exercise: A review of recent preclinical studies

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…In contrast, acute exercise is aimed at transiently enhancing blood flow to the tumor, thereby reducing hypoxia [ 46 ]. Aerobic exercise regulates AMPK signaling, PI3K/Akt signaling, Th1/Th2 cytokine balance related to immunity, PD-1/PD-L1 immunosuppressive signaling, and related cytokine pathways for antitumor effects [ 47 ].…”
Section: Perspectives Of Applications: Qigong Exercise Generates Oxyg...mentioning
confidence: 99%
“…In contrast, acute exercise is aimed at transiently enhancing blood flow to the tumor, thereby reducing hypoxia [ 46 ]. Aerobic exercise regulates AMPK signaling, PI3K/Akt signaling, Th1/Th2 cytokine balance related to immunity, PD-1/PD-L1 immunosuppressive signaling, and related cytokine pathways for antitumor effects [ 47 ].…”
Section: Perspectives Of Applications: Qigong Exercise Generates Oxyg...mentioning
confidence: 99%
“…Such findings may have important implications for inhibiting tumor metastasis and improving the study of the role of physical activity and exercise across the entire cancer continuum [ 30 ]. However, the mechanisms by which aerobic exercise inhibits or delays tumorigenesis currently remain elusive, and the study of the relationship between aerobic exercise and tumors requires further investigation to develop more effective clinical treatment regimens [ 29 , 30 , 31 ]. Aerobic exercise is an alternative method to induce the “oxygen effect” within tumor cells, although clinical studies have shown that it elicits variable effects on oxygen saturation [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus is that exercise is a critical lifestyle habit that has the potential to lower the risk of different cancer types. Preclinical studies on exercise have concluded on the protective effect of exercise against cancer ( Jia et al, 2021 ; Jee et al, 2022 ). In rodents, physical activity interventions, such as swimming, treadmill running, and wheel running, show reduced tumor growth, incidence, and metastasis across a variety of chemically and genetically induced tumor models ( Jia et al, 2021 ; Jee et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies on exercise have concluded on the protective effect of exercise against cancer ( Jia et al, 2021 ; Jee et al, 2022 ). In rodents, physical activity interventions, such as swimming, treadmill running, and wheel running, show reduced tumor growth, incidence, and metastasis across a variety of chemically and genetically induced tumor models ( Jia et al, 2021 ; Jee et al, 2022 ). In humans, differential sensitivity to physical activity has been observed based on the genetic background of the cancer type ( Jones et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%